Development Application for Harbour Mobile Crane Feasibility Evaluation at PT Berlian Jasa Terminal Indonesia Surabaya - Arif, Abdurrakhman; Setyawan, Henry Bambang; Susilo, Tegar Heru (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
PT Berlian Jasa Terminal Indonesia is a company engaged in the areas of services and stevedoring services in the port area. Where the main production equipment used is Harbour Mobile Crane (HMC). With a very expensive price and feasibility calculation process that is still limited trust. It can be difficult for the mechanic to explain the performance of existing machines to the managerial. So may harm the company because it can be swelling expenditures in case of late taking a decision.Writer try to made an application that can compute the value of the performance of a machine along with its economic value. The function of this application is to assess the feasibility of the two sides are assessed in terms of performance and assessed in terms of the economy. In terms of performance, the engine will be assessed by the MTTR and MTBF. The point is to get the value of the Availability and Reability.From an economic perspective, the machine will be assessed based on the value of assets and the cost of care. The votes of the two terms of the application will provide an assessment of whether the machine is still fit for use or not.